Evolution, time, production and the environment - Faber, Malte; Proops, John L. R. (Springer Berlin Heidelberg Imprint: Springer, 1993)
This book is concerned with the long-run interactions between the economy and the natural environment. Part II explores and develops the concept of evolution, in particular distinguishing between evolution which does not involve the emergence of novelty, and evolution where novelty does occur. In Part III three types of time irreversibility are developed, and these concepts are used to show how time has been treated in the natural sciences, and also to typify various schools of economic thought. Part IV addresses the problem of "ignorance" in philosophy and science, particularly with respect to the conceptualization, study and solution of environmental problems. Part V is concerned with the economic modelling of the above concepts. It extends and adapts neo-Austrian capital theory to provide a basis for the modelling of long-run economy-environment interactions. A heuristic simulation model is described, and its simulation results are discussed. Part VI draws some lessons from the earlier discussion and analysis. It also stresses the role and the importance of interdisciplinary work for the understanding of relationships between economic activity and the natural environment